The asymmetric impact of decision-making confidence on regret and relief - Liu, Zan (Frontiers in Psychology, 2024)
When individuals make uncertain decisions, they often evaluate the correctness of their choices in what is referred to as decision-making confidence. The outcomes of such decision-making can lead to counterfactual thinking wherein alternative possible outcomes are contemplated. This, in turn, can elicit counterfactual emotions including upward and downward counterfactual thinking, which respectively refer to regret and relief. Decision-making confidence and counterfactual emotions have key effects on how individuals learn from the past and prepare for the future. However, there has been little understanding of how these experiences are related. For this study, 98 total adults were recruited with the goal of assessing the connections between decision-making confidence and sensations of regret and relief when completing a cardbased gambling task. The results of this study suggest that decision-making confidence may reduce the intensity of relief while increasing the degree of regret experienced. These findings thus emphasize the important effect that decision confidence has on emotional processing.